Pengaruh Pemilihan Eksplan Dan Varietas Terhadap Induksi Kalus Tanaman Tebu (Saccharum Officinarum L) - Mardiana, Yushi; Dwi Putriani, Laili; Setyo Utomo, Pamuji (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
Tissue culture is one of the appropriate plant propagation methods for producing superior seeds in large numbers and simultaneously. The aim of this research was to determine the effect of selecting different explants and varieties on callus induction in sugar cane plants. This research was carried out from March to May 2022 at the Tissue Culture Laboratory of the Sugar Research Center (Puslit) PTPN X Jengkol, Plosokidul Village, Plosoklaten District, Kediri Regency. The method used in this research was a Completely Randomized Design (CRD) which was arranged factorially with two replications. The first factor is the explant part of the sugar cane shoot (E) which consists of 6 levels, namely the 1st, 3rd, 5th, 7th, 9th and 11th pieces. The second factor is the types of varieties with different ripeness types (V) which consist of 3 levels, namely NX 01 (early ripe), Cenning (middle ripe), and PSDK 923 (slow ripe). Based on the data analysis that has been carried out, the results obtained are that the combination of treatment of sugarcane shoot explant parts (E) and varieties (V) shows a positive response to the callus emergence time variable with the fastest callus emergence being the combination of the 1st explant cutting treatment on the NX variety 01 with an average of 6.5 days. A single treatment of sugarcane shoot explant parts (E) had a very significant effect on the contamination percentage variable. The lowest contamination percentage observed in 11-th piece as 8,35%.